Tingkat Pemahaman Siswa SDN 016 Sawit Permai Terhadap Dampak Bullying - Amanda, Fanaya; Khoerunnisa, Isna; Andria, Muhammad Luthfillah; Ermal, Dini Aulia Sari (LPPM UMRI, 2026)
Bullying is aggressive behavior repeatedly carried out by individuals or groups with greater power against weaker individuals, with the intention of causing harm. For victims, bullying can lead to a loss of self-confidence, while for perpetrators, such behavior may become habitual and reinforced by their environment. This study aimed to examine the effectiveness of anti-bullying socialization activities in increasing students’ awareness and understanding of the dangers of bullying at SDN 016 Sawit Permai. The research employed a quantitative experimental method using a One Group Pretest–Posttest design. The sample consisted of 30 fifth- and sixth-grade students selected through purposive sampling. Data were analyzed using a paired t-test. The results showed a significant difference between pretest and posttest scores, with a Sig. (2-tailed) value of 0.000 < 0.05, indicating that H₀ was rejected. The mean posttest score (9.6) was substantially higher than the mean pretest score (5.17). These findings demonstrate a significant improvement in students’ understanding after the intervention. Therefore, anti-bullying socialization programs are proven to be effective as a preventive strategy for fostering a safe, comfortable, and conducive school environment that supports students’ development.